Silicone sealant with high extrudability and good shaping ability and preparation method thereof

By using powder modifiers with specific structures in silicone sealants, the problem of insufficient shaping ability of silicone sealants when improving mechanical strength and extrusion properties is solved, and the consideration of high extrusion properties and shaping ability is achieved. Suitable for rapid continuous construction.

CN115873554BActive Publication Date: 2024-12-24GUANGZHOU BAIYUN CHEM IND +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211688785.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-27
Publication Date
2024-12-24
Estimated Expiration
2042-12-27

AI Technical Summary

Technical Problem

When existing silicone sealants improve mechanical strength and extrusion, they often fail to take into account both the shaping ability, resulting in the problem of interruption of glue or wire drawing during construction.

Method used

Powder modifiers prepared by platinum catalysts using end-propene polyether glycidyl ether, dihydrogen-terminated polydimethylsiloxane and vinyl trimethoxysilane to combine α,ω-dihydroxypolydimethyl Based on the silicone, crosslinking agent, coupling agent and catalyst, silicone sealant with high extrusion and shaping ability is prepared.

Benefits of technology

Through the use of powder modifiers, the extrusion and thixotropy of powder fillers are improved, and the construction efficiency and construction performance of silicone sealants under high powder filling conditions are ensured, making them suitable for rapid and continuous construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FDA0004828289770000011
    Figure FDA0004828289770000011
  • Figure FDA0004828289770000021
    Figure FDA0004828289770000021
  • Figure GDA0004828289780000021
    Figure GDA0004828289780000021
Patent Text Reader

Abstract

The present invention discloses a silicone sealant with high extrudability and good shaping ability and a preparation method thereof. In parts by weight, the silicone sealant is prepared from raw materials including the following components: α, ω-dihydroxy polydimethylsiloxane: 100 parts, powder filler: 100-150 parts, cross-linking agent: 2-20 parts, coupling agent: 1-10 parts, powder modifier: 0.5-1 part, catalyst: 0.01-2.5 parts; the powder modifier is a mixture prepared by a silylation reaction of terminal propylene polyether glycidyl ether, dihydrogen-terminated polydimethylsiloxane and vinyl trimethoxysilane under the action of a platinum catalyst. The silicone sealant still has good construction extrudability under high powder filling conditions, and at the same time has excellent construction shaping ability, is suitable for fast and continuous construction operations, and improves the actual application construction efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of silicone sealants, in particular to a silicone sealant with high extrudability and good shaping ability and a preparation method thereof. Background Art

[0002] Silicone sealant is made of linear hydroxy polysiloxane, reinforcing powder, crosslinking agent and coupling agent. Compared with polyurethane CN bond, acrylic CC bond, polysulfide CS bond and other polymer molecular chain chemical bond Si-O bond, the bond energy is higher and more flexible, which makes silicone sealant have excellent high and low temperature resistance, UV aging resistance and electrical properties, and is widely used in the construction industry, new energy photovoltaic, energy storage, automobile, electronic and electrical fields.

[0003] Silicone sealants need to have appropriate construction properties while maintaining their excellent application properties, so as to ensure that silicone sealants can be smoothly applied to actual occasions, such as whether the extrudability matches the equipment, whether the thixotropic ability is sufficient for shaping, and whether the operation time meets the process requirements. Due to the weak interaction force of the polysiloxane chain segments, the mechanical strength of the cured product itself is not high. In order to improve the mechanical strength of the cured silicone sealant, the most commonly used reinforcement method is to fill a large amount of reinforcing powder materials into the system, such as nano calcium carbonate, fumed silica, aluminum hydroxide, carbon black, etc. In many continuous production line occasions, sealants are required to have both high extrudability (to prevent continuous construction from breaking the glue) and excellent shaping ability (to prevent flowing or drawing). The addition of reinforcing powder materials will increase the thixotropic shaping ability of the colloid on the one hand, and the fluidity (extrudability) of the formed paste will gradually decrease on the other hand. It is often encountered that when the powder filling amount reaches the requirements of mechanical properties and thixotropic properties, the extrudability of the paste is far from meeting the requirements of rapid extrusion construction; and when the extrudability meets the requirements, the thixotropic shaping ability of the paste cannot meet the requirements. The existing method mainly involves grafting or coating various oils on the surface of the powder to improve the thixotropy and extrusion performance of the sealant paste, but the actual effect on improving the extrusion performance is not very obvious. Summary of the invention

[0004] Based on this, the object of the present invention is to provide a silicone sealant with good extrudability and shaping ability.

[0005] In order to achieve the above object, the present invention includes the following technical solutions.

[0006] A silicone sealant is prepared from raw materials including the following components in parts by weight:

[0007] α, ω-dihydroxy polydimethylsiloxane: 100 parts

[0008] Powder filler: 100-150 parts

[0009] Cross-linking agent: 2-20 parts

[0010] Coupling agent: 1-10 parts

[0011] Powder modifier: 0.5-1 part

[0012] Catalyst: 0.01-2.5 parts;

[0013] The powder modifier is a mixture prepared by a hydrosilylation reaction of acryl-terminated polyether glycidyl ether, dihydrogen-terminated polydimethylsiloxane and vinyl trimethoxysilane under the action of a platinum catalyst;

[0014] The structural formula of the terminal acryl polyether glycidyl ether is as follows:

[0015]

[0016] In some embodiments, the silicone sealant is prepared from raw materials including the following components in parts by weight:

[0017] α, ω-dihydroxy polydimethylsiloxane: 100 parts

[0018] Powder filler: 110-130 parts

[0019] Cross-linking agent: 2-12 parts

[0020] Coupling agent: 1-2 parts

[0021] Powder modifier: 0.5-1 part

[0022] Catalyst: 1 to 2.5 parts.

[0023] In some of the embodiments, the molar ratio of the terminal acryl polyether glycidyl ether, the dihydrogen-terminated polydimethylsiloxane and the vinyltrimethoxysilane is 1:0.9-1.1:0.9-1.1.

[0024] In some embodiments, the average molecular weight of the terminal acryl polyether glycidyl ether is 300-1000, and the epoxy value is 0.1-0.3.

[0025] In some of the embodiments, the average molecular weight of the terminal acryl polyether glycidyl ether is 400-600, and the epoxy value is 0.15-0.24.

[0026] In some of the embodiments, the viscosity of the dihydrogen-terminated polydimethylsiloxane is 25 mPa.s to 500 mPa.s, and the hydrogen content is 0.16 mmol / g to 1.25 mmol / g.

[0027] In some of the embodiments, the viscosity of the dihydrogen-terminated polydimethylsiloxane is 200 mPa.s to 300 mPa.s, and the hydrogen content is 0.16 mmol / g to 0.20 mmol / g.

[0028] In some embodiments, the platinum catalyst is a Custer platinum catalyst.

[0029] In some embodiments, the powder modifier contains a polymer with the following structure:

[0030]

[0031] In some of the embodiments, the preparation method of the powder modifier comprises the following steps: dissolving the dihydrogen-terminated polydimethylsiloxane and the terminal acryl polyether glycidyl ether in a solvent, adding the platinum catalyst, reacting for 4 hours to 8 hours, then adding the vinyltrimethoxysilane and continuing the reaction for 4 hours to 8 hours, and removing the solvent to obtain the powder modifier.

[0032] In some embodiments, the solvent is toluene.

[0033] In some embodiments thereof, the viscosity of the α,ω-dihydroxypolydimethylsiloxane at 25° C. is 10000 mPa.s to 100000 mPa.s.

[0034] In some embodiments thereof, the viscosity of the α,ω-dihydroxypolydimethylsiloxane at 25° C. is 15000-25000 mPa.s.

[0035] In some embodiments, the powder filler is selected from at least one of nano calcium carbonate, light calcium carbonate, heavy calcium carbonate, aluminum hydroxide, fumed silica and precipitated silica.

[0036] In some of the embodiments, the powder filler is nano calcium carbonate, and its average particle size is 80nm to 120nm.

[0037] In some of the embodiments, the filler is a combination of nano calcium carbonate and aluminum hydroxide in a mass ratio of 1:1.5 to 2.5.

[0038] In some embodiments, the average particle size of the nano calcium carbonate is 80nm to 120nm.

[0039] In some embodiments, the average particle size of the aluminum hydroxide is 4 um to 6 um.

[0040] In some embodiments, the crosslinking agent is selected from at least one of methyltributylacetoximosilane, vinyltributylacetoximosilane, phenyltributylacetoximosilane, tetrabutylketoneximosilane, methyltrimethoxysilane and methyltriethoxysilane.

[0041] In some of the embodiments, the coupling agent is selected from at least one of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane.

[0042] In some of the embodiments, the catalyst is selected from at least one of di-n-butyltin dilaurate, di-n-butyltin diacetate, stannous octoate, di-n-butyltin dioctoate, propyl titanate, butyl titanate and titanium chelate.

[0043] The present invention also provides a method for preparing the above-mentioned silicone sealant, which includes the following technical scheme.

[0044] A method for preparing the above-mentioned silicone sealant comprises the following steps:

[0045] (1) adding the α,ω-dihydroxypolydimethylsiloxane, powder filler, and powder modifier into a vacuum kneader, stirring for 30 min to 60 min at a temperature of 50° C. to 70° C., then heating to 140° C. to 160° C., stirring for 120 min to 180 min at a vacuum degree of -0.090 MPa to -0.100 MPa, and cooling to obtain a base material;

[0046] (2) putting the base material and the cross-linking agent into a planetary mixer and stirring for 10 min to 20 min under a vacuum degree of -0.090 MPa to -0.100 MPa;

[0047] (3) Add the silane coupling agent and the catalyst into a planetary mixer, and stir for 60 min to 90 min under a vacuum degree of -0.090 MPa to -0.100 MPa to obtain the silicone sealant.

[0048] The silicone sealant with high extrudability and good shaping ability of the present invention has the following advantages and beneficial effects:

[0049] The invention uses terminal acryl polyether glycidyl ether, dihydrogen-terminated polydimethylsiloxane and vinyl trimethoxysilane as raw materials to prepare a mixture of polyether containing reactive functional groups and siloxane segment polymers through a hydrosilylation reaction under the action of a platinum catalyst, further uses the polymer as a powder modifier to modify the powder filler, and prepares a silicone sealant with high extrudability and good shaping ability by combining α, ω-dihydroxy polydimethylsiloxane and a certain amount of crosslinking agent, coupling agent and catalyst.

[0050] The present invention uses a polymer containing a reactive functional group polyether and a siloxane segment of a specific structure to graft and modify the powder filler, wherein the siloxane segment and the polyether segment are grafted or coated onto the surface of the nano powder to increase the free volume of the powder surface, thereby improving the extrusion ability of the system; in addition, the hydrogen bond network formed by the polyether segment in the system can effectively improve the thixotropic ability of the colloid; and the prepared silicone sealant is combined with α, ω-dihydroxy polydimethylsiloxane and a certain amount of a crosslinking agent, a coupling agent and a catalyst to ensure that the prepared silicone sealant still has good construction extrusion under high powder filling conditions, and has excellent construction shaping ability, is suitable for rapid and continuous construction operations, and improves the actual application construction efficiency. DETAILED DESCRIPTION

[0051] The technical scheme of the present invention is further illustrated by specific examples below. Those skilled in the art should understand that the examples are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0052] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0053] The terms "including" and "having" and any variations thereof of the present invention are intended to cover non-exclusive inclusions. For example, a process, method, device, product or equipment comprising a series of steps is not limited to the listed steps or modules, but may optionally include steps not listed, or may optionally include other steps inherent to these processes, methods, products or equipment.

[0054] In the present invention, the term "multiple" refers to two or more than two. "And / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent the following three situations: A exists alone, A and B exist at the same time, and B exists alone. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0055] The viscosity in the present invention refers to the viscosity under the test condition of 25°C.

[0056] The normal temperature described in the present invention refers to the indoor temperature of 18°C-35°C.

[0057] Example 1

[0058] The silicone sealant with high extrudability and good shaping ability provided in this embodiment is prepared from the following raw materials in parts by weight:

[0059] 20000mPa.sα,ω-dihydroxy polydimethylsiloxane: 100 parts

[0060] Nano calcium carbonate with an average particle size of 100 nm: 120 parts

[0061] Methyl trisbutyl ketoxime silane: 9 parts

[0062] Vinyl trisbutyl ketoxime silane: 3 parts

[0063] γ-Aminopropyltriethoxysilane: 2 parts

[0064] Di-n-butyltin dilaurate: 0.2 parts

[0065] Powder modifier: 0.6 parts.

[0066] The preparation method of the powder modifier is as follows: dissolve an equal molar amount of dihydrogen-terminated polydimethylsiloxane (viscosity of 250 mPa.s, hydrogen content of 0.18 mmol / g) and terminal acryl polyether glycidyl ether (average molecular weight of 500, epoxy value of 0.18) in toluene, add 5 ppm Custer platinum catalyst (based on the mass of platinum), react at room temperature for 6 hours, then add an equal molar amount of vinyl trimethoxy silane and continue to react for 6 hours, then remove the solvent in vacuo to obtain a light yellow viscous liquid, that is, the powder modifier. The main reaction formula is as follows:

[0067]

[0068] The preparation method of the silicone sealant with high extrudability and good shaping ability in this embodiment is as follows:

[0069] (1) Add α,ω-dihydroxypolydimethylsiloxane, powder filler, and powder modifier into a vacuum kneader, control the temperature to 60°C, stir at high speed (35-40 r / min) for 45 minutes, continue to heat to 150°C, start vacuum, the vacuum degree is -0.090 to -0.100 MPa, stir at high speed (35-40 r / min) for 150 minutes, and cool to room temperature to obtain a base material.

[0070] (2) The base material and cross-linking agent are placed in a planetary mixer, cooled with water and kept at room temperature, with a vacuum degree of -0.090 to -0.100 MPa, a rotation speed of 18 Hz, and stirred for 15 minutes.

[0071] (3) Add silane coupling agent and catalyst into a planetary mixer, control the mixture under room temperature with water cooling, vacuum degree -0.090 to -0.100 MPa, rotation speed 18 Hz, and stir for 75 min to obtain a sealant.

[0072] Example 2

[0073] The silicone sealant with high extrudability and good shaping ability provided in this embodiment is prepared from the following raw materials in parts by weight:

[0074] 20000mPa.sα,ω-dihydroxy polydimethylsiloxane: 100 parts

[0075] Nano calcium carbonate with an average particle size of 100 nm: 120 parts

[0076] Methyltrimethoxysilane: 3 parts

[0077] γ-(2,3-Epoxypropoxy)propyltrimethoxysilane: 1.5 parts

[0078] Catalyst organic titanium Tyzor726 alkoxy titanate chelate: 2 parts

[0079] Powder modifier: 0.6 parts.

[0080] The preparation method of the silicone sealant with high extrudability and good shaping ability in this embodiment is as follows:

[0081] (1) Add α,ω-dihydroxypolydimethylsiloxane, powder filler, and powder modifier (same as in Example 1) into a vacuum kneader, control the temperature to 60°C, stir at high speed (35-40 r / min) for 45 min, then continue to heat to 150°C, open the vacuum, the vacuum degree is -0.090 to -0.100 MPa, stir at high speed (35-40 r / min) for 150 min, and cool to room temperature to obtain a base material.

[0082] (2) The base material and cross-linking agent are placed in a planetary mixer, cooled with water and kept at room temperature, with a vacuum degree of -0.090 to -0.100 MPa, a rotation speed of 18 Hz, and stirred for 15 minutes.

[0083] (3) Add silane coupling agent and catalyst into a planetary mixer, control the mixture under room temperature with water cooling, vacuum degree -0.090 to -0.100 MPa, rotation speed 18 Hz, and stir for 75 min to obtain a sealant.

[0084] Example 3

[0085] The silicone sealant with high extrudability and good shaping ability provided in this embodiment is prepared from the following raw materials in parts by weight:

[0086] 20000mPa.sα,ω-dihydroxy polydimethylsiloxane: 100 parts

[0087] Nano calcium carbonate with an average particle size of 100 nm: 40 parts

[0088] Aluminum hydroxide with an average particle size of 5um: 80 parts

[0089] Methyltrimethoxysilane: 3 parts

[0090] γ-(2,3-Epoxypropoxy)propyltrimethoxysilane: 1.5 parts

[0091] Catalyst organic titanium Tyzor726 alkoxy titanate chelate: 2 parts

[0092] Powder modifier: 1.0 part.

[0093] The preparation method of the silicone sealant with high extrudability and good shaping ability in this embodiment is as follows:

[0094] (1) Add α,ω-dihydroxypolydimethylsiloxane, powder filler, and powder modifier (same as in Example 1) into a vacuum kneader, control the temperature to 60°C, stir at high speed (35-40 r / min) for 45 min, then continue to heat to 150°C, open the vacuum, the vacuum degree is -0.090 to -0.100 MPa, stir at high speed (35-40 r / min) for 150 min, and cool to room temperature to obtain a base material.

[0095] (2) The above base material and cross-linking agent are placed in a planetary mixer, cooled with water and kept at room temperature, with a vacuum degree of -0.090 to -0.100 MPa, a rotation speed of 18 Hz, and stirred for 15 minutes.

[0096] (3) Add silane coupling agent and catalyst into a planetary mixer, control the mixture under room temperature with water cooling, vacuum degree -0.090 to -0.100 MPa, rotation speed 18 Hz, and stir for 75 min to obtain a sealant.

[0097] Comparative Example 1

[0098] The silicone sealant with high extrudability and good shaping ability provided in this comparative example is prepared from the following raw materials in parts by weight:

[0099] 20000mPa.sα,ω-dihydroxy polydimethylsiloxane: 100 parts

[0100] Nano calcium carbonate with an average particle size of 100 nm: 120 parts

[0101] Methyl trisbutyl ketoxime silane: 9 parts

[0102] Vinyl trisbutyl ketoxime silane: 3 parts

[0103] γ-Aminopropyltriethoxysilane: 2 parts

[0104] Di-n-butyltin dilaurate: 0.2 parts.

[0105] The preparation method of the silicone sealant of this embodiment is as follows:

[0106] (1) Add α,ω-dihydroxypolydimethylsiloxane and powder filler into a vacuum kneader, control the temperature to 60°C, stir at high speed (35-40 r / min) for 45 minutes, continue to heat to 150°C, start vacuum, the vacuum degree is -0.090 to -0.100 MPa, stir at high speed (35-40 r / min) for 150 minutes, and cool to room temperature to obtain a base material.

[0107] (2) The above base material and cross-linking agent are placed in a planetary mixer, cooled with water and kept at room temperature, with a vacuum degree of -0.090 to -0.100 MPa, a rotation speed of 18 Hz, and stirred for 15 minutes.

[0108] (3) Add silane coupling agent and catalyst into a planetary mixer, control the mixture under room temperature with water cooling, vacuum degree -0.090 to -0.100 MPa, rotation speed 18 Hz, and stir for 75 min to obtain a sealant.

[0109] Comparative Example 2

[0110] The silicone sealant with high extrudability and good shaping ability provided in this comparative example is prepared from the following raw materials in parts by weight:

[0111] 20000mPa.sα,ω-dihydroxy polydimethylsiloxane: 100 parts

[0112] Nano calcium carbonate with an average particle size of 100 nm: 120 parts

[0113] Methyltrimethoxysilane: 3 parts

[0114] γ-(2,3-Epoxypropoxy)propyltrimethoxysilane: 1.5 parts

[0115] Catalyst organic titanium Tyzor726 alkoxy titanate chelate: 2 parts.

[0116] The preparation method of the silicone sealant with high extrudability and good shaping ability in this embodiment is as follows:

[0117] (1) Add α,ω-dihydroxypolydimethylsiloxane and powder filler into a vacuum kneader, control the temperature to 60°C, stir at high speed (35-40 r / min) for 45 minutes, continue to heat to 150°C, start vacuum, the vacuum degree is -0.090 to -0.100 MPa, stir at high speed (35-40 r / min) for 150 minutes, and cool to room temperature to obtain a base material.

[0118] (2) The above base material and cross-linking agent are placed in a planetary mixer, cooled with water and kept at room temperature, with a vacuum degree of -0.090 to -0.100 MPa, a rotation speed of 18 Hz, and stirred for 15 minutes.

[0119] (3) Add silane coupling agent and catalyst into a planetary mixer, control the mixture under room temperature with water cooling, vacuum degree -0.090 to -0.100 MPa, rotation speed 18 Hz, and stir for 75 min to obtain a sealant.

[0120] Example 4

[0121] The silicone sealant samples prepared in the above-mentioned Examples 1-3 and Comparative Examples 1-2 were subjected to key performance tests, especially the extrusion and droop related to construction, as well as the mechanical strength, tensile strength, elongation at break, and hardness of the colloid after curing. The cured test samples were tested after the molds were cured for 7 days in a ventilated environment at 25±2°C and 50±10%RH. The extrusion test was conducted in accordance with the GB / T 13477.4-2002 test method, wherein the pressure was 0.2±0.01MPa, the diameter of the glue nozzle was 4±0.02mm, and the glue bottle was a 300ml glue bottle. The droop was tested in accordance with the GB / T 13477.6-2002 test method; the tensile strength and elongation at break were determined according to the national standard GB / T 528-2009 type 1 sample preparation; the hardness was tested in accordance with the provisions of GB / T 531.1. The test results are shown in Table 1.

[0122] Table 1 Performance comparison of silicone sealants in various embodiments and comparative examples

[0123]

[0124] From the results in Table 1, it can be seen that after adding the powder modifier in the base material refining process in Examples 1, 2, and 3, the extrusion index of the finished sealant is significantly improved compared with Comparative Examples 1 and 2 (without adding the modifier). This means that under the same sizing extrusion equipment conditions, the silicone sealant products prepared in Examples 1, 2, and 3 have better construction performance, providing the possibility of doubling the construction efficiency.

[0125] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0126] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A silicone sealant, characterized in that: The composition is prepared from the following raw materials in parts by weight: α, ω-dihydroxy polydimethylsiloxane: 100 parts Powder filler: 100-150 parts Cross-linking agent: 2-20 parts Coupling agent: 1-10 parts Powder modifier: 0.5-1 part Catalyst: 0.01-2.5 parts; The powder modifier is a mixture prepared by a hydrosilylation reaction of acryl-terminated polyether glycidyl ether, dihydrogen-terminated polydimethylsiloxane and vinyl trimethoxysilane under the action of a platinum catalyst; The structural formula of the terminal acryl polyether glycidyl ether is as follows:

2. The silicone sealant according to claim 1, characterized in that: The composition is prepared from the following raw materials in parts by weight: α, ω-dihydroxy polydimethylsiloxane: 100 parts Powder filler: 110-130 parts Cross-linking agent: 2-12 parts Coupling agent: 1-2 parts Powder modifier: 0.5-1 part Catalyst: 1 to 2.5 parts.

3. The silicone sealant according to claim 1, characterized in that: The molar ratio of the terminal acryl polyether glycidyl ether, the dihydrogen-terminated polydimethylsiloxane and the vinyl trimethoxysilane is 1:0.9-1.1:0.9-1.

1.

4. The silicone sealant according to claim 1, characterized in that: The average molecular weight of the terminal acryl polyether glycidyl ether is 300 to 1000, and the epoxy value is 0.1 to 0.3; and / or, The dihydrogen-terminated polydimethylsiloxane has a viscosity of 25 mPa.s to 500 mPa.s and a hydrogen content of 0.16 mmol / g to 1.25 mmol / g; and / or, The platinum catalyst is a Custer platinum catalyst.

5. The silicone sealant according to claim 4, characterized in that: The average molecular weight of the terminal acryl polyether glycidyl ether is 400 to 600, and the epoxy value is 0.15 to 0.24; and / or, The viscosity of the dihydrogen-terminated polydimethylsiloxane is 200 mPa.s to 300 mPa.s, and the hydrogen content is 0.16 mmol / g to 0.20 mmol / g.

6. The silicone sealant according to any one of claims 1 to 5, characterized in that: The powder modifier contains a polymer with the following structure:

7. The silicone sealant according to any one of claims 1 to 5, characterized in that: The preparation method of the powder modifier comprises the following steps: dissolving the dihydrogen-terminated polydimethylsiloxane and the terminal acryl polyether glycidyl ether in a solvent, adding the platinum catalyst, reacting for 4 to 8 hours, then adding the vinyltrimethoxysilane and continuing the reaction for 4 to 8 hours, and removing the solvent to obtain the powder modifier.

8. The silicone sealant according to any one of claims 1 to 5, characterized in that: The viscosity of the α,ω-dihydroxy polydimethylsiloxane at 25° C. is 10,000 to 100,000 mPa.s; and / or, The powder filler is selected from at least one of nano calcium carbonate, light calcium carbonate, heavy calcium carbonate, aluminum hydroxide, fumed silica and precipitated silica; and / or, The crosslinking agent is selected from at least one of methyltributylacetoximosilane, vinyltributylacetoximosilane, phenyltributylacetoximosilane, tetrabutylketoximesilane, methyltrimethoxysilane and methyltriethoxysilane; and / or, The coupling agent is selected from at least one of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane; and / or, The catalyst is selected from at least one of di-n-butyltin dilaurate, di-n-butyltin diacetate, stannous octoate, di-n-butyltin dioctoate, propyl titanate, butyl titanate and titanium chelate.

9. The silicone sealant according to claim 8, characterized in that: The viscosity of the α,ω-dihydroxy polydimethylsiloxane at 25° C. is 15000 mPa.s to 25000 mPa.s; and / or, The powder filler is a combination of nano calcium carbonate and aluminum hydroxide in a mass ratio of 1:1.5-2.5; and / or, The average particle size of the nano calcium carbonate is 80nm to 120nm; and / or, The average particle size of the aluminum hydroxide is 4um to 6um.

10. A method for preparing the silicone sealant according to any one of claims 1 to 9, characterized in that: The steps include: (1) adding the α,ω-dihydroxypolydimethylsiloxane, powder filler, and powder modifier into a vacuum kneader, stirring for 30 min to 60 min at a temperature of 50° C. to 70° C., then heating to 140° C. to 160° C., stirring for 120 min to 180 min at a vacuum degree of -0.090 MPa to -0.100 MPa, and cooling to obtain a base material; (2) putting the base material and the cross-linking agent into a planetary mixer and stirring for 10 min to 20 min under a vacuum degree of -0.090 MPa to -0.100 MPa; (3) Add the silane coupling agent and the catalyst into a planetary mixer, and stir for 60 min to 90 min under a vacuum degree of -0.090 MPa to -0.100 MPa to obtain the silicone sealant.